DA draws a circle: on document architecture and its relation to library and information science education and research - Mats Dahlstrom; Mikael Gunnarsson (Information Research: An International Electronic Journal, 2000)
The architectural metaphor used in analyzing compound meta-objects such as referential databases might be applied also to the primary records these referential tools point to, thereby making way for the study of document architecture (DA). Library and information science has by and large been focussing on possible ways of determining the meanings of the objects of "input", whereas the materiality and the textual structure of the objects have been regarded as transparent, offering little or no room for problematization and discussion. The article argues for a revaluation of this somewhat delimiting perspective. Digital production and distribution reframe the ways in which objects and meta-objects might be construed. The mismatch of traditional library institutions and systems (where the printed codex book and its derivatives have been the standard of measurement) and digital carriers for bodies of text and the different architectures of these, suggests our great need for new fields of LIS research, where DA might prove a valuable tool. DA studies might also be useful in re-theorizing traditional reading and writing technologies and their conditioning of textual carriers.